Effect of Midnight Prayer on Sympathetic Tone - Hadiyatussalamah Pusfa Kencanasari; Achmad Fauzi Yahya; Setiawan Setiawan (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Hypertension is one of the most dangerous ailments which most common risk factor is stress that can activate sympathetic system leading to increased blood pressure. Midnight prayer is believed to calm mind. This study was conducted to discover the effect of midnight prayer on sympathetic tone.Methods: This cross sectional study was conducted in Bina Siswa Senior High SchoolSMA Plus Cisarua Boarding School, Lembang from October to November 2013. Sixty eight participants were divided into 3 groups based on frequency; high, low, and non midnight prayer. Blood pressure and pulse rate of participants were examined before, during, and after the cold pressor test is taken. Blood pressure and pulse rate duration of recovery were also measured.Results: This study showed no significant difference between 3 groups in term of systolic blood pressure, diastolic blood pressure, and pulse rate. However, the lowest mean of pulse rate (64.38±8.921 vs 66.69±11.482 vs 65.44±9.584 respectively), systolic blood pressure [107.19±6.945 vs 117.13±13.426 vs 104.25 (75–120) respectively], and diastolic blood pressure [70.38±7.719 vs 77.38±10.935 vs 70.63±7.491 respectively] were obtained in the high midnight prayer group. Recovery duration of blood pressure [6.38 (6–8) vs 6.72 (6–11) vs 6.75 (6–11) respectively] and pulse rate (6.69±0.946 vs 7.03±1.341 vs 7.00±1.506 respectively) among the groups showed no significant difference respectively, however the shortest duration was obtained in the high midnight prayer group.Conclusions: Midnight prayer has no significant effect on sympathetic tone. [AMJ.2016;3(1):59–63]DOI: 10.15850/amj.v3n1.692